Mixed Offspring in the Hebrew Bible and Second Temple Period - Gabizon, Michael (My University, 2022)
My dissertation analyzes the status of mixed offspring in the Hebrew Bible and Second Temple texts to understand the diverse ways children from intermarried couples were presented in pre-Mishnaic Jewish literature. Prior to the Mishnah (m. Qidd 3:12), there is no evidence of a monolithic ruling to regulate the status of mixed progeny. My goal, therefore, is to examine the different ways mixed offspring were treated, and to better understand whether they endured any social repercussions due to their mixed lineage. In turn, I explore the diverse ways Jewish identity was constructed in antiquity, and how matters like gender, lineage, and geography were used to establish social boundaries. Within contemporary scholarship, the study of mixed progeny in antiquity has been incidental to other research topics, including the expulsion narrative in Ezra 9–10, genealogical purity, and the matrilineal principle in Judaism. To date, no comprehensive approach has been undertaken to trace the status of mixed progeny in pre-Mishnaic Jewish literature. My dissertation seeks to fill this lacuna. Following a brief introduction in chapter 1, my subsequent chapters are divided into four time periods: the pre-Persian period (chapter 2); the Persian period (chapter 3); the Hellenistic period (chapter 4); and the early Roman period (chapter 5). Within each chapter, I analyze texts generally dated to those eras that include some information about mixed offspring. In my concluding chapter, I reveal three main factors that impacted the status of mixed progeny in antiquity: genealogy, residential location, and piety. I also provide a heuristic framework to categorize my findings of mixed offspring. While there were two main responses towards mixed progeny in antiquity (accepted or rejected), not every case fits nicely into these two classifications. Therefore, the treatment of mixed progeny must be understood on a spectrum to better appreciate the nuance within each text.
Keywords: Mixed offspring; intermarriage; Second Temple Judaism; Identity; Hebrew Bible; Gender; Child-centered; Dead Sea Scrolls; Philo; Josephus; Jubilees; Purity; Profane; exogamy